2020
DOI: 10.3390/jrfm14010008
|View full text |Cite
|
Sign up to set email alerts
|

Civic Crowdfunding in Local Governments: Variables for Success in the Netherlands?

Abstract: By using information technology, local governments can develop alternative forms of citizen engagement. Civic crowdfunding campaigns supported by online platforms enable citizens to participate financially in social projects and can be matched with government funding. As such, an alternative for subsidies seems to be developing. In this paper, we assess empirically the success of civic crowdfunding campaigns in the Netherlands by using data collected during 2018 from 269 civic crowdfunding projects and local d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In this sense, the current literature, although limited in scope so far, provides overall positive outcomes when it comes to investing private or public funds to complete positively evaluated crowdfunding calls. In a recent study, Van Montfort et al (2021) found that civic crowdfunding projects matched with extra funds by local governments does increase the chances of success.…”
Section: Types Of Matchfunding and The Incentive Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the current literature, although limited in scope so far, provides overall positive outcomes when it comes to investing private or public funds to complete positively evaluated crowdfunding calls. In a recent study, Van Montfort et al (2021) found that civic crowdfunding projects matched with extra funds by local governments does increase the chances of success.…”
Section: Types Of Matchfunding and The Incentive Mechanismmentioning
confidence: 99%
“…The literature on the matchfunding model via crowdfunding platforms is still in its infancy. Recent studies demonstrate that partnering with governments or other external funds tends to increase the success of crowdfunding calls (Montfort, Siebers and De Graaf, 2021). NESTA previously implemented a famous pilot study based on the platform Crowdfunder, whose results demonstrate how matchfunding calls are more likely to succeed compared to non-matchfunding calls within the crowdfunding system (Baeck et al, 2017).…”
Section: Types Of Matchfunding and The Incentive Mechanismmentioning
confidence: 99%
“…Crowdfunding is viewed as a prospective fundraising method, as a smaller amount of money is collected from a larger number of people (Van Montfort et al., 2021). Crowdfunding takes many forms like, equity crowdfunding, debt crowdfunding, reward based crowdfunding and donation crowdfunding.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the registered status of the NPOs, the literature on charitable giving provides evidence that tax-deduction on eligible donations also reflects legitimacy and motivates people to donate (Auten et al 2002;Brown 1999;Morgan et al 1979). However, the literature on crowdfunding has not examined the impact of signals that incentivize donations for social causes (Van Montfort et al 2021). André et al (2017) study reciprocal giving from the perspective of theory by Mauss (1923) and show that reward-based crowdfunding projects that have an element of reciprocal giving are more successful than other campaigns.…”
Section: Signalling Legitimacymentioning
confidence: 99%